Kualitas Pelayanan Pendaftaran Tanah Sistematis Lengkap (PTSL) Pada Kantor Pertanahan Kabupaten Hulu Sungai Utara - Arpandi (STIA Bina Banua Banjarmasin, 2025)
This research is to determine the quality of Complete Systematic Land Registration (PTSL) Services at the North Hulu Sungai Regency Land Office. This research conducted qualitative research and used descriptive-qualitative type as an approach. Interviews, documentation, and observation are data collection methods. The results of the research can be concluded that the quality of the Complete Systematic Land Registration Service at the Hulu Sungai Utara Regency Land Office is of sufficient quality as seen in: Sub variable reliability indicator for ease of information, sub variable responsiveness indicator for providing services quickly, sub variable guarantee indicator timeliness, cost certainty. The optimal indicators can be seen in the sub-variables in the form of indicators of physical facilities, equipment, sub-variables of reliability, indicators of clear service standards, sub-variables of responsiveness, indicators of the accuracy and accuracy of officers, sub-variables of empathy, indicators of officers being friendly, officers being polite.